Modeling of syngas composition obtained from fluidized bed gasifiers using Kuhn–Tucker multipliers - Amaro, Jordan [UNESP]; Mendiburu, Andrés Z. [UNESP]; Ávila, Ivonete [UNESP] (Elsevier, 2018)
This work aims to develop a modified chemical equilibrium model to accurately determine the syngas (synthesis gas) composition obtained from fluidized bed gasifiers. In order to do so, an optimization method was applied to determine the correction factors which modify the chemical equilibrium constants, the carbon conversion efficiency and the enthalpy of reaction. The gasification agents considered for this study were: air, steam, air–steam, and air–steam–oxygen. The optimization method used the Kuhn–Tucker multipliers to obtain small RMS errors. A total of 76 experimental compositions of syngas were selected. Among these data 60 were used to obtain correlations for the correction factor, the carbon conversion efficiency and the enthalpy of reaction. Then, a modified chemical equilibrium model was formulated by a taking advantage of these correlations. The modified chemical equilibrium model was validated showing very good accuracy for the determination of the syngas composition, the RMS error were found to be between 0.94 and 4.84.
Keywords: Fluidized bed; Gasification; Modified chemical equilibrium model